Потомки Эа-илута-бани (из истории средних слоев нововавилонского общества - Белявский, В. A.
Beljavskij, V. А.; The Descendants of Ēa-ilūta-bāni (from the history of the middle strata of New Babylonian society); engl. Résumé.